Rethinking Virtual Learning Environments in Resource-Constrained Contexts: Student Interaction, Effectiveness, and Digital Inequality in Latin American Higher Education - Ticona, Jorge Apaza; et al. (European Journal of Social Science Education and Research, 2026)
Virtual Learning Environments (VLEs) have become a central component of contemporary higher education; however, their effectiveness in resource-constrained contexts remains insufficiently examined. This study investigates the determinants of student experience, interaction, and perceived effectiveness of VLEs among undergraduate students in the Faculty of Social Sciences at the National University of the Altiplano (Peru). A quantitative, cross-sectional design was employed, using a stratified random sample of 112 students enrolled in semesters four through eight. Data were analyzed through descriptive and correlational techniques to identify patterns, relationships, and key factors influencing learning outcomes. The findings reveal a predominantly positive perception of VLEs (57.1%), particularly regarding access to educational resources and the facilitation of student–instructor interaction. Nevertheless, important structural and pedagogical challenges persist. A significant proportion of students (50.9%) reported recurrent technical difficulties, while 38.4% perceived virtual learning as less effective than traditional face-to-face instruction. Teaching practices were largely mediated through videoconferencing platforms—primarily Zoom and Google Meet—indicating a platform-dependent instructional model with limited pedagogical diversification and reduced use of interactive or student-centered strategies. Moreover, gaps in personalized feedback, disparities in digital competencies, and insufficient institutional support mechanisms were identified as critical barriers to effective learning. These limitations suggest that access to technology alone is not sufficient to ensure meaningful educational experiences. This study contributes to the literature by providing context-sensitive empirical evidence from a public university in a resource-limited Latin American setting. It highlights the need to strengthen the integration of technological infrastructure with pedagogical innovation, emphasizing interaction design and student engagement. Accordingly, targeted institutional strategies are required to develop inclusive, adaptive, and pedagogically robust virtual learning ecosystems that respond effectively to the needs of underserved higher education contexts.